Logistics Information and Communication Technology - Kubasakova, Iveta; Kampf, Rudolf; Stopka, Ondrej (Communications - Scientific letters of the University of Zilina, 2014)
As technology costs decline and usage becomes easier, logistics managers are managing information electronically at lower logistics expense with increased coordination results in enhanced services by offering better information and services to customers. This article deals with logistics information system, which is to be used in company. Logistics information system (LIS) must have a good structure for every company. LIS characteristics as availability, accuracy, timelines, exception-based LISs, flexibility and appropriate format are described in article.